Protocol for the REPAT study: role of emotional processing in art therapy for breast cancer palliative care patients. Issue 11 (19th November 2020) - Czamanski-Cohen, Johanna; Wiley, Joshua; Weihs, KL
Abstract : Introduction: Patients with breast cancer (BC) cope with depression which is linked to functional limitations in survivorship and to physical symptoms. Pain and fatigue are prominent symptoms that affect the well-being of cancer survivors. Emotional processing has been associated with improved physical and psychological health in survivors. Art therapy is a form of psychotherapy that involves the use of visual art-making for expression and communication. It encourages emotional processing and has been linked to symptom reduction in patients with cancer. This protocol is designed to examine two mechanistic changes: emotional processing (awareness, expression and acceptance) and cholinergic anti-inflammatory processes (heart rate variability and cytokine expression) through which an art therapy intervention may reduce depression, pain and fatigue. In addition, we will examine ethnocultural differences in the effect of art therapy in women from different ethnocultural backgrounds. Methods and analysis: A randomised controlled study with careful controls will randomise 240 patient with BC (50% Jewish and 50% Arab) to an 8-week group art therapy intervention or an 8-week Mandala colouring comparison group. This design will test the mechanisms of art therapy on the targeted outcomes beyond the effects of time with a group, focus on a task and engagement with art materials. We will examine two potential mechanisms: emotional processing and cholinergic anti-inflammatory processes; of the intervention effects on depression, pain and fatigue and compare these effects in Arab versus Jewish women. Ethics and dissemination: Participants will sign informed consent before participation and will be informed that they can leave the study at any point in time without effect on their medical treatment. The Helsinki committees of each participating hospital have approved the study. Data collected in this study will be published in peer-review journals, and we will use the platform of the study website (http://repat.haifa.ac.il/en/ ) for further dissemination to the general public. Trial registration number: The study is registered in ClinicalTrials.gov: NCT03377816 ; Pre-results.